AN ANALYSIS OF LANGUAGE STYLES USED BY NADIEM MAKARIM IN SINGAPORE SUMMIT 2020 - Taufik Ramadan; Istianatul Hikmah; Novita Sumarlin Putri; Poppy Indriyanti (Universitas Sarjanawiyata Tamansiswa, 2022)
This research is conducted in order to analyze the language styles which are used by Nadiem Makarim in Singapore Summit 2020. This research is used talk-show as the source of data. The object of this research is the utterances of Nadiem Makarim which is delivered in Singapore Summit YouTube channel. This study is analyzed the language styles and the language function uttered by Nadiem Makarim using Martin Joos and Janet Holmes theory. Nadiem Makarim utterance was intentionally chosen as a research object because the researcher found that the data was interesting and also can contribute to the comprehensive understanding related to language styles and language functions. In addition, Nadiem Makarim was chosen because he is one of many people who can use an English language close to a native speaker. In order to make systematically analysis, the researcher will use qualitative descriptive method